EVALUATING THE IMPACT OF ELECTRONIC HEALTH RECORDS ON PATIENT CARE QUALITY AND CLINICAL DECISION-MAKING PROCESSES (Global Conference on Medical and Health Sciences, 2026)
The digital transformation of healthcare has accelerated significantly over the past decades, with Electronic Health Records (EHR) becoming a central component of modern medical practice. EHR systems enable the systematic collection, storage, and sharing of patient information, thereby improving clinical workflows, patient safety, and decision-making processes. This study aims to comprehensively evaluate the impact of EHR systems on patient care quality and clinical decision-making. A mixed-methods approach was employed, combining quantitative performance analysis with qualitative insights from healthcare professionals. The findings demonstrate that EHR implementation significantly improves diagnostic accuracy, reduces medical errors, enhances efficiency, and supports evidence-based decision-making. However, challenges such as interoperability limitations, clinician workload, and cybersecurity risks remain critical barriers. Overall, EHR systems represent a transformative advancement in healthcare, but their effectiveness depends on proper implementation, training, and technological integration.
Keywords: Electronic Health Records, EHR, patient care, clinical decision-making, healthcare quality, digital health, medical informatics